2015
DOI: 10.15252/embj.201490805
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin O ( Ccno ) functions during deuterosome‐mediated centriole amplification of multiciliated cells

Abstract: Mucociliary clearance and fluid transport along epithelial surfaces are carried out by multiciliated cells (MCCs). Recently, human mutations in Cyclin O (CCNO) were linked to severe airway disease. Here, we show that Ccno expression is restricted to MCCs and the genetic deletion of Ccno in mouse leads to reduced numbers of multiple motile cilia and characteristic phenotypes of MCC dysfunction including severe hydrocephalus and mucociliary clearance deficits. Reduced cilia numbers are caused by compromised gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
105
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 30 publications
(50 reference statements)
13
105
4
Order By: Relevance
“…Although CCNO partners and function are unknown, patients with mutations in ccno have MCCs with reduced number of cilia ). In particular, ccno mutant mice tracheal cells display larger deuterosomes with fewer proBBs suggesting a role for CCNO in the early onset of amplification (Funk et al 2015).…”
Section: Molecular Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Although CCNO partners and function are unknown, patients with mutations in ccno have MCCs with reduced number of cilia ). In particular, ccno mutant mice tracheal cells display larger deuterosomes with fewer proBBs suggesting a role for CCNO in the early onset of amplification (Funk et al 2015).…”
Section: Molecular Controlmentioning
confidence: 99%
“…1) (Stubbs et al 2012;Ma et al 2014;Wallmeier et al 2014), a cyclin-like protein first shown to be involved in oocyte meiosis resumption and apoptosis (Roig et al 2009;Ma et al 2013), and then shown to be expressed in MCC progenitors in the Xenopus skin and in the mouse brain, airways, and oviducts (Stubbs et al 2012;Funk et al 2015;Amirav et al 2016). Although its partners and molecular function remain to be determined, CCNO mutations or depletion lead to defects comparable to the C-MYB phenotype: defects in BB amplification, docking, and ciliogenesis Funk et al 2015). In humans, mutations in CCNO have been identified as a cause of RGMC and associated with hydrocephalus and female infertility Amirav et al 2016).…”
Section: Downstream Effectors Of the MCC Differentiation Programmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Foxn4 needs to be re-examined in mouse MCCs, especially as partial genetic redundancy in the pathways that drive MCC differentiation has become a recurring theme. For example, mutations in two crucial regulators of MCC differentiation, namely Ccno and Myb, cause severe defects in MCC differentiation in the mouse lung initially but also eventually recover, at least superficially, over time (Funk et al, 2015;Tan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%